Electroacupuncture attenuates liver and kidney oxidative stress in anesthetized rats - Silva,Agamenon Honório (2011)
PURPOSE: Investigate the effects of a single electroacupuncture (EA) session at acupoints Zusanli (ST-36) and Zhongwan (CV-12) combined in regulating oxidative stress in liver and kidney in anesthetized rats. METHODS: Eighteen healthy rats randomly assigned to 3 groups (n=6) were anesthetized intraperitoneally with ketamine (90mg kg-1 body weight) + xylazine (10mg/kg body weight): G-1: Control (anesthesia), G-2: anesthesia+EA10Hz and 10 mA, 10 Hz) applied to right ST-36 and CV-12 acupoints for 30 minutes. G-3 was likewise treated, using a tenfold higher frequency (100 Hz). G6PDH activity, malondialdehyde (MDA) and glutathione (GSH) levels were assayed spectrophotometrically. RESULTS: Liver MDA and GSH concentrations increased significantly in rats submitted to EA 10Hz (p<0.01) and EA 100Hz (p<0.001), compared with control G-1. Liver and kidney G6GPH activity decreased significantly in G-2 (p<0.01) and G-3 (p<0.001) compared with G-1 in EA100Hz rats. A similar pattern was found in kidney G6PDH activity in EA10Hz rats. CONCLUSION: Single 30-minute EA 10/100Hz session enhances lipid peroxidation and simultaneously reduces oxidative stress in liver and kidney tissues in a rat model.